Valorization of the red macroalga Gracilaria corticata by hydrothermal liquefaction: Product yield improvement by optimization of process parameters. (September 2021) - Fernandes, Alisha C.; Biswas, Bijoy; Kumar, Jitendra; Bhaskar, Thallada; Muraleedharan, Usha D.
Abstract: Hydrothermal liquefaction (HTL) of the red alga Gracilaria corticata was carried out at 260, 280 and 300 °C for 15 min using H2 O as solvent. The bio-oil yield was maximal (5.25 wt%) at 300 °C. Influence of the solvents methanol, ethanol, acetone and ethanol-water on the distribution as well as nature of the resultant HTL products has also been examined. Organic solvents could markedly improve the bio-oil yield to over 16 wt%. Bio-oil and biochar were characterized through FT-IR, GC–MS and 1 H NMR studies. Analysis of GC–MS data in conjunction with FT-IR and 1 H NMR derived information revealed that the bio-oil mainly consisted of various derivatives of compounds such as aldehydes, ketones, phenols, acids and esters, besides nitrogenous compounds. This research outcome using HTL as a technique for enhancing bio-oil yield, in particular from red macroalgae, would provide a stimulus for further investigations on potential commercial applications of algal bio-oil. Graphical abstract: Unlabelled Image Highlights: HTL of the red alga G. corticata was performed to obtain biooil and other products. HTL was carried out at different temperatures and with different solvents. Use of acetone and alcoholic solvents in place of water improved bio-oil yield. Composition of bio-oil varied with solvent type as per GCMS, FTIR, NMR analysis.